The Implementation of Outcome Based Education to Support Student Understanding and Performance in the Internet of Things Course - Undayani Cita Sari; Bagus Hario Setiadji; Amelia Kusuma Indriastuti; Banu Ardi Hidayat; Danang Dwi Admojo (Journal of Education Technology, 2024)
Outcome Based Education (OBE) is a learning method that focuses on outcomes in a learning process. In the field of engineering, the delivery of lecture materials coupled with the achievement of targets for outcomes is a challenge, especially when it comes to technology applications. This is because the application of technology requires real examples, so that the students can have a comprehensive picture and understanding. This study was carried out on the Internet of Things (IoT) course at Undergraduate Program in Civil Engineering, Faculty of Engineering. This course discusses the basics of applying IPTEKS (Science, Technology and Arts) tools that can be utilized in the field of Civil Engineering, especially in the current Industrial Revolution 4.0. This research was intended to evaluate the OBE implementation, in terms of student participation and level of understanding of students. Observations were made during one semester by observing the results of student evaluations and the feedback received by the lecturers. The evaluation was carried out qualitatively and quantitatively based on the course learning outcomes (CLO). The results showed that all students actively participate in the learning process using this OBE method. The high level of material understanding was indicated by the achievement of a 100% passing rate, but there were still two students who have not fulfilled two CLOs. Therefore, continuous improvement efforts are still needed in implementing OBE for students, so that all students can fulfill all CLOs in Internet of Things courses.